Pengenalan Model Pembelajaran Situation Based Learning dalam Pembelajaran Matematika pada Guru SMAN 2 Cibitung - Lestari, Indah; Andinny, Yuan; Ramdani, Irham (Presisi Jurnal Pengabdian Masyarakat, 2023)
This community service activity carried out at SMAN 2 Cibitung aims to provide knowledge and understanding of the Situation Based Learning learning model. To become a qualified and professional educator, teachers at the secondary school level are required to have a variety of skills and expertise to support teaching and learning activities in schools. Mathematics is one of the subjects that is frightening for students, most students think that mathematics is difficult. Teachers must be able to make this difficult assumption disappear, because if at school students don't like mathematics, then at the next higher level students will be increasingly afraid of mathematics lessons. That's why creative learning can be fun for students, teachers will be able to build students' liking for mathematics if they are able to provide fun learning. The Situation Based Learning learning model will help teachers in organizing creative and fun learning for students, so it is hoped that students will enjoy learning mathematics if teachers use this Situation Based Learning learning model.